Electromagnetic torque performance evaluation of concentric magnetic gear alternative conditions using finite element - Mohd Ab Halim, Mohd Firdaus; Ab Rahman, Azhan; Sulaiman, Erwan; Aziz, Roziah; Othman, Syed Muhammad Naufal; Naufal, Syed Muhammad; Kosaka, Takashi (Universiti Malaysia Perlis, 2021)
Concentric magnetic gear (CMG) research mainly focuses on the CMG act as torque increaser and with stationary pole piece condition. Yet, technically CMG can be designed as speed increaser gear with the alternative rotating condition. This paper investigates an initial torque performance of CMG in alternative conditions operating as torque increaser and speed increaser gear. The conditions are when either the inner pole pair or outer pole pair is set stationary while the pole piece component act as rotors. The structure and working principle of the motor are described in detail. The torque performance from finite element software, JMAG Designer 16.0 simulation, as compared with the conventional condition and discussed briefly. The result showed that the conventional condition generates a minor percentage of torque ripple at 1.52%. The highest gear ratio is achieved when the pole piece serves as the outer rotor. Abnormality was also discovered in the conventional condition when the gear operates as a speed increaser. This study concludes that the CMG functions better as a torque increaser instead of a speed increaser gear.